Parallel efficient global optimization method: A novel approach for time-dependent reliability analysis and applications. (1st December 2021) - Wu, Jiawei; Jiang, Zhenliang; Song, Huaming; Wan, Liangqi; Huang, Fu
Graphical abstract: Highlights: Parallel efficient global optimization and adaptive Kriging-Monte Carlo simulation were integrated. The proposed method outperformed the existing methods in computing efficiency. The proposed method showed an excellent accuracy in high-dimension problems. Abstract: Time-dependent failure may result from material properties deterioration, random load, and other uncertain factors, which are widespread among practical engineering applications. However, in previous studies of time-dependent reliability analysis (TRA), parallel computing, which can speed up the optimization process significantly, has not been fully considered. Therefore, this study proposed a parallel efficient global optimization (PEGO) integrated with the adaptive Kriging-Monte Carlo simulation (AK-MCS) for the TRA problems. It was shown that the proposed method was superior to the existing TRA methods in computing efficiency and maintained a high accuracy to solve the high-dimension of the TRA problems. Besides, it exhibited an extensive application scope due to the excellent performances (i.e., efficiency, accuracy), which were verified via six representative cases, including four low-dimension and two high-dimension, by comparing with the existing TRA methods.